Upcycling natural Limestone waste for thermochemical energy storage by utilising tailored CaZrO3 nanoadditives. Issue 8 (8th March 2023) - Anwar, Rehan; Navrátil, Jan; Vijayaraghavan, Rajani K.; McNally, Patrick J.; Otyepka, Michal; Błoński, Piotr; Sofianos, M. Veronica
Abstract : Enabling the carbonation reaction of Limestone waste by using CaZrO3 nanoadditives. Abstract : The development of long-term renewable energy storage systems is crucial for decarbonising the energy sector and enabling the transition to a sustainable energy future. Thermochemical energy storage (TCES) systems are well suited for long-term renewable energy storage as the materials used in these systems have high energy densities, and long storage duration. Among the plethora of TCES materials, calcium carbonate (Limestone) is of particular interest since it exhibits a high enthalpy of reaction, and it is earth-abundant. The main problem with Limestone inhibiting its commercial application for long-term renewable energy storge is its deteriorating cycling performance after several energy charge/discharge cycles. In this study, two CaZrO3 nanoadditives with two different Ca : Zr ratios and tailored oxygen vacancies were synthesised by a precipitation method, and mixed with Limestone waste at three weight concentrations (5, 10 and 20 wt%). Their phase, chemical state and morphology were determined by XRD, XPS and TEM, respectively. The cycling performance of the mixture samples was determined through thermogravimetric analysis. The best performing sample was the one mixed with 20% CaZrO3 nanoadditives, which contained a large number of oxygen vacancies and thus had enhanced ionic conductivity, as confirmed by density functional theory (DFT) calculations. This sample exhibited the best effective conversion and the highest energy density values of 0.7 and 2640 kJ kg −1, respectively, after 40 cycles.